Unguided virtual-reality training can enhance the oral presentation skills of high-school students - Valls-Ratés, Ïo; Niebuhr, Oliver; Prieto, Pilar (Frontiers in Communication, 2022)
Public speaking is fundamental in our daily life, and it happens to be challenging for many people. Like all aspects of language, these skills should be encouraged early on in educational settings. However, the high number of students per class and the extensive curriculum both limit the possibilities of the training and, moreover, entail that students give short in-class presentations under great time pressure. Virtual Reality (VR) environments can help speakers and teachers meet these challenges and foster oral skills. This experimental study employs a between-subjects pre- and post-training design with four Catalan high-school student groups, a VR group (N=30) and a Non-VR group (N=20). Both groups gave a 2-minute speech in front of a live audience before (pre-training) and after (post-training) 3 training sessions (one session per week) in which they practiced public speaking either in front of a VR audience or alone in a classroom (Non-VR). Students assessed their anxiety measures right before performing every speech and completed a satisfaction questionnaire at the end. Pre- and post-training speeches were assessed by 15 raters, who analyzed the persuasiveness of the message and the charisma of the presenter. Speeches were also analyzed for prosodic features and gesture rate. First, results showed that self-assessed anxiety got significantly reduced at post-training for both conditions. Second, acoustic analyses of both groups’ speeches show that the VR group has, unlike the Non-VR group, developed a more clear and resonant voice quality in the post-training speeches, in terms of higher cepstral-peak prominence (CPP) (although no significant differences in f0- related parameters were obtained), as well as significantly less erosion effects. However, these differences across groups did not trigger a direct improvement on the participants’ gesture rate, persuasiveness and charisma at post-training. Furthermore, students perceived the training in the VR environment to be more useful and beneficial for their future oral presentations than the Non-VR group. All in all, short unguided VR training sessions can help students feel less anxious, promote a more clear and resonant voice style, and can prevent them from experiencing an erosion effect while practicing speeches in front of a real audience.